Follow-up of patients with thyroglobulin-antibodies: Rising Tg-Ab trend is a risk factor for recurrence of differentiated thyroid cancer. (2nd October 2017) - de Meer, Siegrid G. A.; Vorselaars, Wessel M. C. M.; Kist, Jakob W.; Stokkel, Marcel P. M.; de Keizer, Bart; Valk, Gerlof D.; Borel Rinkes, Inne H. M.; Vriens, Menno R.
ABSTRACT: Purpose : Differentiated thyroid cancer is the most common endocrine malignancy. Recurrences (5–20%) are the main reason for follow-up. Thyroglobulin (Tg) has proven to be an excellent disease marker, but thyroglobulin-antibodies (Tg-Ab) may interfere with Tg measurement, leading to over or underestimation. It is proposed that the Tg-Ab trend can be used as a marker for disease recurrence, yet few studies define trend and have a long-term follow-up. The objective of our study was to investigate the value of a well-defined Tg-Ab trend as a surrogate marker for disease recurrence during long-term follow-up.Methods : We retrospectively studied patients treated at the Nuclear Department of the University Medical Center Utrecht from 1998 to 2010 and the Netherlands Cancer Institute from 2000 to 2009. All patients with Tg-Ab 12 months after treatment were included. The definition of a rise was >50% increase of the Tg-Ab value in a 2 year time period. A decline as >50% decrease of the Tg-Ab value.Results : Twenty-five patients were included. None of the patients with declining or stable Tg-Ab without a concomitant rise in Tg developed a recurrence. Four patients did suffer a recurrence. Three of these patients had a rising Tg-Ab trend, in two of these patients Tg was undetectable.Conclusions : Tg-Ab trend can be used as a crude surrogate marker for long-term follow-up of Tg-Ab patients. A rising trend in Tg-Ab warrants further investigation to detect recurrent disease. Stable or declining Tg-Ab levels do not seem to reflect a risk for recurrence.